2023
DOI: 10.1097/mco.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet in cancer management

Abstract: Purpose of reviewThis review presents details about types of ketogenic diet (KD), anticancer mechanisms, and the use of KD in experimental and clinical studies. Studies summarized in this review provide a solid ground for researchers to consider the use of KD to augment conventional treatments.Recent findingsKD is a dietary pattern composed of high fat, moderate proteins, and very-low-carbohydrate. This diet was suggested to have an anticancer effect and to augment conventional anticancer therapies. KD can tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Notably, various forms of the KD have been developed to address different clinical demands, ranging from body weight management to neurological disorders, while recent research has shed light on the potential cardiovascular benefits of a KD [ 5 , 7 , 8 ]. Emerging evidence has suggested that the metabolic and neurobiological effects of the KD extend beyond seizure control, offering potential advantages for cardiovascular health, cancer treatment, and inflammation reduction, while also impacting various aspects of brain function and mental well-being [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, various forms of the KD have been developed to address different clinical demands, ranging from body weight management to neurological disorders, while recent research has shed light on the potential cardiovascular benefits of a KD [ 5 , 7 , 8 ]. Emerging evidence has suggested that the metabolic and neurobiological effects of the KD extend beyond seizure control, offering potential advantages for cardiovascular health, cancer treatment, and inflammation reduction, while also impacting various aspects of brain function and mental well-being [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%